Der Markt fur̈ Bioenergie 2021/2022 - Sor̈en Mohrmann; Sirkka Schukat; Christian Schaper (German Journal of Agricultural Economics (GJAE), 2022)
This year's Bioenergy Market Report provides an overview of current climate and energy policy issues with a focus on Germany. After a sharp decline in the global economy and energy consumption in 2020 due to the COVID-19 pandemic, 2021 is characterized by a slight economic recovery, which has had a corresponding impact on the international energy markets. After outlining the events from 2021 that are relevant to energy policy, renewable energies are contextualized within the German and international energy mix. Along with a description of biomass production in agriculture and forestry, usage of biogenic residual and waste materials is also described. The section on the energetic use of biomass deals with current developments in German biogas production and biofuels markets, as well as electricity and heat generation from biogenic solid fuels. The report concludes with a chapter on agrophotovoltaics as an opportunity for agriculture and the energy transition in Germany.
Keywords: 330